Subarachnoid hemorrhage triggers neuroinflammation of the entire cerebral cortex, leading to neuronal cell death - Hiroki Yamada; Yoshitaka Kase; Yuji Okano; Doyoon Kim; Maraku Goto; Satoshi Takahashi; Hideyuki Okano; Masahiro Toda (Inflammation and Regeneration, 2022)
Abstract Background Subarachnoid hemorrhage (SAH) is a fatal disease, with early brain injury (EBI) occurring within 72 h of SAH injury contributes to its poor prognosis. EBI is a complicated phenomenon involving multiple mechanisms. Although neuroinflammation has been shown to be important prognosis factor of EBI, whether neuroinflammation spreads throughout the cerebrum and the extent of its depth in the cerebral cortex remain unknown. Knowing how inflammation spreads throughout the cerebrum is also important to determine if anti-inflammatory agents are a future therapeutic strategy for EBI. Methods In this study, we induced SAH in mice by injecting hematoma into prechiasmatic cistern and created models of mild to severe SAH. In sections of the mouse cerebrum, we investigated neuroinflammation and neuronal cell death in the cortex distal to the hematoma injection site, from anterior to posterior region 24 h after SAH injury. Results Neuroinflammation caused by SAH spread to all layers of the cerebral cortex from the anterior to the posterior part of the cerebrum via the invasion of activated microglia, and neuronal cell death increased in correlation with neuroinflammation. This trend increased with the severity of the disease. Conclusions Neuroinflammation caused by SAH had spread throughout the cerebrum, causing neuronal cell death. Considering that the cerebral cortex is responsible for long-term memory and movement, suppressing neuroinflammation in all layers of the cerebral cortex may improve the prognosis of patients with SAH.